Anthology of Ukrainian Poetry “Strings” by Bohdan Lepky as a Text in Contextual Reading - Lilia Оvdiichuk (Вісник Харківського національного університету імені В. Н. Каразіна. Серія Філологія. Vìsnik Harkìvsʹkogo nacìonalʹnogo unìversitetu ìmenì V.N. Karazìna. Serìâ Fìlologìâ.)
The anthology of Ukrainian poetry «Strings», compiled by Bohdan Lepky, not only became an important literary phenomenon, a text for reading, but also reflected the aesthetic and cultural aspirations of the era. The relevance of the study is determined by the attention of modern literary studies to the formation of the canon of Ukrainian literature. The anthology as a text is a representative of the "golden fund" of national red literature. It is also timely to identify and analyze the contexts of the creation of this meta-genre.